"All Colors and Hues": An Autoethnography of a Multiethnic Family's Strategies for Bilingualism and Multiculturalism. Issue 1 (22nd January 2013) - Kennedy, Kimberley D.; Romo, Harriett D.
<x xml:space="preserve">Abstract</x> This two‐year autoethnographic action research study explores the processes a multiethnic/multiracial family uses to maintain their children's heritage language of Spanish and the family's multiculturalism. Data sources (including interviews and participant observations in the home and the dual‐language school) specifically focus on the eldest child, Nelia, from her kindergarten and first‐grade years where she attended a public dual‐language program. The findings illuminate the integral link between the family's ideology toward valuing bilingualism and the necessity of school support.